Analysis of Cultivated Land in Maonan District, Maoming Based on RS and GIS - Feng, Shujie; Wang, Ruei-Yuan; Liu, Haolong; Wang, Yun-Shang (International journal of Rural Development, Environment and Health Research, 2023)
Food is the most basic human survival need, and cultivated land is the basis of food production. Thereby, monitoring and analysis of cultivated land is the premise and foundation of sustainable agricultural development. In this paper, Maonan District of Maoming City was taken as the research area. The object-oriented classification and cultivated land extraction were carried out by Landsat-8 remote sensing (RS) images, and then a confusion matrix and kappa coefficient were used to evaluate the accuracy of the cultivated land extraction results. The results show that the cultivated land in this area is decreasing. The extraction results of the confusion matrix and Kappa coefficient evaluation were accurate, and the Kappa coefficients of the three different periods were all higher than 0.6. Moreover, the main reasons for the decrease of cultivated land in the study area are population growth, socio-economic development, and the adjustment and change of agricultural structure.